Effect of Progressive Structured Neuromuscular Training Program on Balance, Performance and Injury Risk Prediction in Amateur Futsal Team Players: Protocol for a Randomized Controlled Trial - Gulay ARAS BAYRAM; Gizem ERGEZEN SAHİN; Devrim TARAKCI; Bilal Deniz AYDOS; Ayten GUNES CELIK; Esra SERTOGULLARINDAN (Romanian Journal of Physical Therapy)
Neuromuscular training improves neuromuscular control and balance, consequently enhancing joint stability. This study aims to assess the impact of a structured neuromuscular training program on balance and performance among university amateur male futsal team players and to analyze biomechanical factors pertinent to injury risk assessments. Thirty athletes aged between 18 and 25, participating in the university male futsal team, will be enrolled in this study. At the outset, all athletes will undergo evaluation using the Korebalance® System, Countermovement Jump, Running-Based Anaerobic Sprint Test, Shot on Goal Test, Sit and Reach Test, Shuttle, Y Balance-Lower Quadrant, and The Tuck Jump test. Subsequently, they will maintain their regular training regimen of classical training twice a week for eight weeks and undergo reassessment using the same battery of tests after 8 weeks of period. Following this initial phase, the athletes will be randomly assigned to two groups: Control Group (n = 15) and Neuromuscular Training Group (n = 15). The Control Group (CG) will continue with their classical futsal training twice a week for eight weeks, while the Neuromuscular Training Group (NMEG) will engage in progressive structured neuromuscular training in addition to their regular futsal training, also twice a week for eight weeks. At the conclusion of the eight-week intervention period, both groups will undergo reevaluation using the same assessment methods. The study commenced in October 2023 and is anticipated to conclude by August 2024. It is anticipated that the integration of progressive structured neuromuscular training into futsal team training programs will yield positive outcomes.